Syair in the Life of Contemporary Malays in Singapore (Malay Literature, 2024)
Syair, a form of traditional Malay poetry believed to have been adapted from the Persian or Arab civilization, has been a popular performative art in the Malay world, including Singapore. It has evolved since its first introduction to the Malay Archipelago with the coming of Islam, and what constitutes as syair today is a culmination of its language structure, aesthetics, and depth of author’s insights as a form of the Malay community’s creative art. Once prevalent amongst the Malays until the 1970s, syair has significantly declined in popularity with the emergence of modern poetry and printed prose, and modern-day forms of entertainment, among other things, though it is still familiar to the urban and contemporary Malays in Singapore. Based on the data collected from a research project (2018 to 2020) in Singapore, this paper demonstrates that syair in the form of rare hikayat (tales) texts and manuscripts are still kept as personal collection and family heirloom. Albeit dwindling in number, the art of syair recital is slowly eroding if not for individuals who perceive the preservation of syair texts and the art of syair recital as their honourable responsibility, akin to preserving the Malays’ social memory and collective wisdom. Full text: PDF